Revista praticando capoeira : materialidade e representações - Silva, Anderson de Freitas (2012)
This study analyses the magazine Praticando Capoeira, understanding it as vestige of a practice net, able to make see the meaning contest in which it was produced and the strength relationship that determinates its structure. The printed matter was produced by the D+T publishing house from 1999, sold mainly in newsstands until 2009, period in which was published 44 editions. By editorial dispositives of the printed matter and by representations elaborated and put to circulate, aimed to understand the world of capoeira, considering it as a social field. A magazine, by its production and circulation agility, can catch aspects of quotidian at the same time that the informations, the conflicts and changes happen. To work with this object that became source of research, it is necessary to consider three distinct elements, which are articulated, considering them as support of texts, besides paying attention to its own texts and to the speeches produced by the chain of meanings in the moment of reading. Based in the Cultural History, and in the reflexions representations struggle, the research understands the collection of magazines as cultural objects that keep the marks of its production. Based in the magazine materiality, work with the periodic using the concept of objects archaeology, in search of clues, to localyze signs of editorial practices, able to reveal the vestiges of strategies used by editors to organization and regulation of the printed matter reading. The magazine Praticando Capoeira is a document and a monument on the world of capoeira, a witness of present to the future that provides the recalling of our time. The representations are in the texts and images, materialized in the object by its editorial formulation. We identified that the magazine presents the organization of the field based on capoeira groups and consider the practice of capoeira as one of the elements of Brazilian identity, with sportive and pedagogical potential.